Case reportsSurgical resection with adjuvant brachytherapy in soft tissue sarcoma of the extremity – a case report - Guzik, Grzegorz; Łyczek, Jarosław; Kowalik, Łukasz (Journal of Contemporary Brachytherapy, 2012)
Purpose : Surgery is the major therapeutic method in soft tissue sarcomas of the extremity (E-STS). Treatment of large high-grade tumours, which resection cannot be performed with a wide safe margin, should include complementary radiation and/or chemo-therapy. Hopefully, the use of adjuvant brachytherapy will improve the prognosis of E-STS. Case description : After a long process of diagnosing a tumour in the medial compartment of the thigh, a 65-year-old woman with diagnosed synovial sarcoma underwent a surgery. Compartment resection was performed and the tumour was removed with a 10 mm safety margin of healthy tissue. Adjuvant brachytherapy was delivered with 192 Ir (MicroSelectron, Nucletron Electa Group, Stockholm, Sweden ® ) with 10 Ci of nominal activity to a dose of 55 Gy in 16 days because of large tumour size (99 × 78 × 73 mm) and its proximity to the neurovascular bundle. No complications were reported. The patient was discharged from the hospital on the 28 th day after the surgery. The wound healed without any complications and the outpatient follow-up is being continued. Discussion : Adjuvant brachytherapy is rarely used after surgical treatment due to its limited accessibility in hospitals with surgical and orthopaedic departments. There are numerous publications proving positive influence of brachytherapy on local control and decreased number of recurrences. The recurrence-free survival time also increased significantly, however no direct impact on the number of distant metastases was found. Treatment is well tolerated and short. The complication rate varies between centres from 5 to 30%. The most common adverse effects include: peripheral neuropathy, skin necrosis and osteonecrosis of the long bones. Conclusions : Treatment of large soft tissue sarcomas of the extremity (E-STS) should include combination of surgical intervention and external beam radiotherapy or brachytherapy. Adjuvant brachytherapy improves local control rate up to 78%, is well tolerated and rarely causes complications. We couldn’t determine which type of adjuvant radiation therapy is more effective.